Molecular Identification of Dibothriocephalus nihonkaiense Infection Using Nanopore Sequencing: A Case Report and Literature Review - Hin-Fung Tsang; Stanley W.M. Leung; Tin-Nok Hung; Icy Law; Ka-Wai Lam; Loiston Chan; Sze-Chuen Cesar Wong (Diagnostics)
Background: Dibothriocephalus nihonkaiense (previously known as Diphyllobothrium nihonkaiense) infection is not common in Hong Kong. D. nihonkaiense is a fish-borne cestode parasite that infects humans after consuming raw or insufficiently cooked fish containing plerocercoids. Case presentation: We reported a case of D. nihonkaiense infection in a 40-year-old woman who presented with a complaint of epigastric pain and diarrhea. A curvilinear opacity was seen at the upper quadrant of the abdomen via abdominal X-ray. An incomplete 80 cm long strobila of D. nihonkaiense without a scolex and neck was found in her feces. A grayish-brown oval egg with an inconspicuous operculum and small knob at the abopercular end was also found. Species-level identification was performed using Nanopore sequencing. Complete blood count and serum vitamin B12 level were tested to check for megaloblastic anemia and vitamin B12 deficiency, respectively. Laboratory investigations demonstrated an elevated percentage of monocytes in peripheral blood. A single oral dose of praziquantel (25 mg/kg) was prescribed to the patient. There was no evidence of relapse after the treatment. Conclusions: We reported a case of D. nihonkaiense infection using Oxford Nanopore NGS as a tool for accurate parasite identification.